Stock photos of the Medford/Somerville campus, including the outside of Tisch Library, East Hall, Dowling Hall, Carmichael Hall, and the Hillel Center. Photo 036 - Loeb, Brian (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including the outside of Tisch Library, East Hall, Dowling Hall, Carmichael Hall, and the Hillel Center.